Schirmer strip vs. capillary tube method: Non-invasive methods of obtaining proteins from tear fluid - Posa, Andreas; Braeuer, Lars; Schicht, Martin; Garreis, Fabian; Beileke, Stephanie; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2013)
Human tear fluid is a complex mixture containing over 500 solute proteins, lipids, electrolytes, mucins, metabolites, hormones and desquamated epithelial cells as well as foreign substances from the ambient air. Little is known to date about the function of most tear components. The efficient and gentle collection of tear fluid facilitates closer investigation of these matters. The objective of the present paper was to compare two commonly used methods of obtaining tear fluid, the capillary tube and Schirmer strip methods, in terms of usefulness in molecular biological investigation of tear film. The comparative protein identification methods Bradford and Western Blot were used in the analyses to this end. The surfactant proteins (SP) A-D recently described as present on the eye surface were selected as the model proteins. Both methods feature sufficient uptake efficiency for proteins in or extraction from the sampling means used (capillary tube/Schirmer strip). The total protein concentration can be determined and the proteins in the tears can be detected - besides the hydrophilic SP-A and D also the non-water-soluble proteins of smaller size such as SP-B and C. Thus both methods afford a suitable basis for comparative analysis of the physiological processes in the tear fluid of healthy and diseased subjects. On the whole, the Schirmer strip has several advantages over the capillary tube. © 2012 Elsevier GmbH.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Capillary tube method; Dry eye; Proteomics; Schirmer strip; Surfactant proteins; Tear fluid